A legal analysis of patient - physician conflicts in accessing medical records: a comparative study between Malaysia and the United Kingdom / Mohamad Aiman Mutallib Mohamad Shariff, Siti Nurliana Mohd Zulkafli and Syahidah Huzaifah Ahmad Sukri - Mohamad Shariff, Mohamad Aiman Mutallib; Mohd Zulkafli, Siti Nurliana; Ahmad Sukri, Syahidah Huzaifah (Faculty of Law, 2012)
The project paper will legally analyse the conflicts between the patient and the physician in accessing the medical records in Malaysia and the United Kingdom. The research paper consists of five fundamental chapters. Chapter One is Introduction, which will be divided into Research Background, Research Question, Research Objectives, Research Methodology, Scope of the Research, Limitation to the Research, and Significance of the Research. Chapter Two is Literature Review. In this chapter, there are three different and important frameworks that are going to be discussed. They are conceptual framework, legal framework and theoretical framework. These three frameworks need to be discussed in order to analyse and highlight the problems that arise between the patient and the physician regarding the issue of accessibility of the medical record. Chapter Three is Interviews. In this chapter, we provided our interviews with two significant respondents in order to be cognizant of their personal views and perspectives concerning the problems that arise between the patient and the physician regarding the issue of accessibility of the medical record. For the aim of the interviews, we prepared eight fundamental questions with respect to the issue in question for the respondents to be personally answered. Chapter Four is Results & Findings. In this chapter, we are going to analyse and scrutinise the results and findings of previous two interviews with the two respondents on the issue of the problems that arise between the patient and the physician regarding the issue of accessibility of the medical record. Finally, Chapter Five is Recommendations & Conclusions. In this chapter, we are going to provide several recommendations which we think may help to minimize the conflicts between the patients and the physicians in accessing the medical records, as well as the conclusions regarding the issues concerned.